Socio-economic Dynamics of Land Ownership Pattern in Rural Western Rajasthan - Purohit, M L; Kalla, Jagdeesh C (Annals of Arid Zone, 2016)
An attempt was made to locate, the differences in patterns of land ownership in two villages selected from two representative land management systems. The results of present study indicated that sizable, inter-caste, inter-temporal and inter-village differences in the land ownership patterns exist in arid regions. The study indicates the insufficiency of the efforts of recent post-Independence past to mitigate the resource ownership differences. Additionally a combination of rigid caste structure and population increase has contributed to this situation. The social, economic and political power base of the existing rural elite has also been a considerable hinderance in rational implementation of land reform programme in this region.